A Systematic Review and Meta-Analysis of the Relationship Between Hospital Volume and the Outcomes of Percutaneous Coronary Intervention. Issue 5 (February 2016) - Lin, Xiaojun; Tao, Hongbing; Cai, Miao; Liao, Aihua; Cheng, Zhaohui; Lin, Haifeng
Abstract : Abstract: Previous reviews have suggested that hospital volume is inversely related to in-hospital mortality. However, percutaneous coronary intervention (PCI) practices have changed substantially in recent years, and whether this relationship persists remains controversial. A systematic search was performed using PubMed, Embase, and the Cochrane Library to identify studies that describe the effect of hospital volume on the outcomes of PCI. Critical appraisals of the methodological quality and the risk of bias were conducted independently by 2 authors. Fourteen of 96 potentiality relevant articles were included in the analysis. Twelve of the articles described the relationship between hospital volume and mortality and included data regarding odds ratios (ORs); 3 studies described the relationship between hospital volume and long-term survival, and only 1 study included data regarding hazard ratios (HRs). A meta-analysis of postoperative mortality was performed using a random effects model, and the pooled effect estimate was significantly in favor of high volume providers (OR: 0.79; 95% confidence interval [CI], 0.72–0.86; P < 0.001). A systematic review of long-term survival was performed, and a trend toward better long-term survival in high volume hospitals was observed. This meta-analysis only included studies published after 2006 and revealed that postoperative mortality following PCI correlates significantly and inversely with hospital volume. However, the magnitude of the effect of volume on long-term survival is difficult to assess. Additional research is necessary to confirm our findings and to elucidate the mechanism underlying the volume–outcome relationship. Abstract : Supplemental Digital Content is available in the text